2001
DOI: 10.4319/lo.2001.46.3.0623
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of methylmercury to the water column of a drainage lake: The relative importance of internal and external sources

Abstract: We studied fluxes of methylmercury (MeHg) through a Precambrian Shield lake using a mass balance approach. The primary goal of the study was to determine the importance of various sources of MeHg to the water column of the lake. The relative importance of all sources was: in-lake production ϾϾϾ inflow from a brown-water lake with riparian wetlands ϾϾϾ wet deposition Ͼ inflow from an upstream oligotrophic lake Ͼ direct inflow from uplands surrounding the lake. MeHg accumulated in the hypolimnion of Lake 240 whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
107
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 26 publications
(27 reference statements)
10
107
3
Order By: Relevance
“…There could also be other sinks of MeHg within the estuary, such as photodegradation. In a recent study, Sellers et al (2001) showed that MeHg removal by photodegration in Canadian lakes is greater than the loss through outflow. However, it is unclear whether photodegration is an important loss mechanism of MeHg in an estuarine environment.…”
Section: Sources Of Mehg-thementioning
confidence: 99%
“…There could also be other sinks of MeHg within the estuary, such as photodegradation. In a recent study, Sellers et al (2001) showed that MeHg removal by photodegration in Canadian lakes is greater than the loss through outflow. However, it is unclear whether photodegration is an important loss mechanism of MeHg in an estuarine environment.…”
Section: Sources Of Mehg-thementioning
confidence: 99%
“…12−14 It was reported that photodegradation could remove a large proportion of the MeHg loading into lake water. 15,16 Since its importance was demonstrated, 14 several researchers have attempted to mechanistically determine the MeHg photodegradation process in aquatic environments. 17−20 Although wavelength-specific photodegradation of MeHg has been observed in aquatic environments, 13,21 much remains unclear about the chemical processes governing MeHg photodegradation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Anaerobic zones in sediments, hypolimnia, and wetlands are the most important sites of microbial methylation, and a water body can receive MeHg from both internal and external sites (Watras et al 1994, Sellers et al 2001. Wetlands are important sites of MeHg production and export to adjacent or downstream waters (Hurley et al 1995, St. Louis et al 1996, Sellers et al 2001, Wiener et al 2006). Concentrations of MeHg in phytoplankton, zooplankton, and higher trophic levels can also be influenced by biodilution of MeHg at the base of the food web by algal blooms or high algal biomass (Pickhardt et al 2002.…”
Section: Mercury In Aquatic Ecosystems and Food Websmentioning
confidence: 99%
“…Such processes include the production of MeHg via the microbial methylation of inorganic Hg II (Benoit et al 2003) and the destruction of MeHg by photodemethylation (Sellers et al 1996(Sellers et al , 2001) and microbial demethylation (Oremland et al 1991, Marvin-DiPasquale et al 2000. Anaerobic zones in sediments, hypolimnia, and wetlands are the most important sites of microbial methylation, and a water body can receive MeHg from both internal and external sites (Watras et al 1994, Sellers et al 2001. Wetlands are important sites of MeHg production and export to adjacent or downstream waters (Hurley et al 1995, St. Louis et al 1996, Sellers et al 2001, Wiener et al 2006).…”
Section: Mercury In Aquatic Ecosystems and Food Websmentioning
confidence: 99%